2015
DOI: 10.1071/an13424
|View full text |Cite
|
Sign up to set email alerts
|

Correlations among various blood parameters at exsanguination and their relationships to pork quality traits

Abstract: The objectives of this study were to investigate the correlations between various blood parameters compared with cortisol and lactate levels under the standard pre-slaughter procedure and handling conditions and to assess their potential as indicators of pork quality traits. Despite there being no additional pre-slaughter stress treatment, there is considerable variation in blood parameters at exsanguination. Serum cortisol and blood lactate levels, widely used indicators of stress, were positively correlated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 39 publications
2
10
0
Order By: Relevance
“…Serum cortisol is widely used as an indicator of stress (Choe et al, 2014). In the present study, the levels of this hormone were similar and not differentiated among groups.…”
Section: Resultssupporting
confidence: 48%
“…Serum cortisol is widely used as an indicator of stress (Choe et al, 2014). In the present study, the levels of this hormone were similar and not differentiated among groups.…”
Section: Resultssupporting
confidence: 48%
“…Therefore, the slaughter of pigs without rest or after short lairaging (15-60 minutes) is not recommended, because animals are exhausted and agitated (Vermeulen et al, 2015). The oxygen demand for aerobic glycogen depletion in acutely stressed pigs cannot be satisfied due to the decrease in blood supply to muscles, which contributes to higher production of lactic acid through the anaerobic metabolic pathway and elevates muscle temperature (+1 °C), consequently increasing the occurrence of PSE meat (Choe et al, 2015). The primary purpose of lairage is to help animals to recover from transport-associated stress, and it is expected to improve meat quality (Guàrdia et al, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…This is because pigs are inevitably exposed to handling, loading, transportation, unloading, adverse weather conditions, mixing with unfamiliar animals, and physical and emotional stress owing to the new accommodation [6]. Preslaughter stress influences body homeostasis and metabolism, resulting in alterations in the physiometabolic blood profile (electrolytes, hormones, metabolites, and enzymes), subsequently decreasing carcass and meat quality [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Stress metabolites, such as blood lactate and glucose, can be useful indicators for assessment of preslaughter stress, and their high blood levels indicate accelerated rate and greater extent of postmortem muscle metabolism, resulting in low muscle pH, while carcass temperature remains high, thus causing the higher prevalence of pale, soft, and exudative (PSE) pork [10,11]. It has been reported that adrenocorticotropic hormone (ACTH) [12] and cortisol [7] are useful indicators of the stress level experienced by pigs during the preslaughter period. Although several studies have investigated the relationship between cortisol concentration and pork quality, the results are not consistent.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation